Factors affecting patterns of Amblyomma triste (Acari: Ixodidae) parasitism in a rodent host - Colombo, Valeria Carolina (2015)
Here we offer a multivariable analysis that explores associations of different factors (i.e., environmental, host parameters, presence of other ectoparasites) with the interaction of Amblyomma triste immature stages and one of its main hosts in Argentina, the rodent Akodon azarae. Monthly and for two years, we captured and sampled rodents at 16 points located at 4 different sites in the Parana River Delta region. The analyses were conducted with Generalized Linear Mixed Models with a negative binomial response (counts of larvae or nymphs). The independent variables assessed were: (a) environmental: trapping year, season, presence of cattle; type of vegetation (natural grassland or implanted forest); rodent abundance; (b) host parameters: body length; sex; body condition; blood cell counts; natural antibody titres; and (c) co-infestation with other ectoparasites: other stage of A. triste; Ixodes loricatus; lice; mites; and fleas. Two-way interaction terms deemed a priori as relevant were also included in the analysis. Larvae were affected by all environmental variables assessed and by the presence of other ectoparasites (lice, fleas and other tick species). Host factors significantly associated with larval count were sex and levels of natural antibodies. Nymphs were associated with season, presence of cattle, body condition, body length and with burdens of I. loricatus. In most cases, the direction and magnitude of the associations were context-dependent (many interaction terms were significant). The findings of greater significance and implications of our study are two. Firstly, as burdens of A. triste larvae and nymphs were greater where cattle were present, and larval tick burdens were higher in implanted forests, silvopastoral practices developing in the region may affect the population dynamics of A. triste, and consequently the eco-epidemiology of Rickettsia parkeri. Secondly, strong associations and numerous interactions with other ectoparasites suggest that co-infestations may be more important for tick dynamics than has so far been appreciated.